Tobacco use in pregnant women: Analysis of data from Demographic and Health Surveys from 54 low-income and middle-income countries - Caleyachetty, R; Tait, CA; Kengne, AP; Corvalan, C; Uauy, R; Echouffo-Tcheugui, JB (Elsevier, 2014)
Background: Worldwide, use of tobacco is viewed as an important threat to the health of pregnant women and their children. However, the extent of tobacco use in pregnant women in low-income and middle-income countries (LMICs) remains unclear. We assessed the magnitude of tobacco use in pregnant women in LMICs.